A Mobile Infliximab Dosing Calculator for Therapy Optimization in Inflammatory Bowel Disease. Issue 2 (18th January 2018) - Piester, Travis; Frymoyer, Adam; Christofferson, Megan; Yu, Helen; Bass, Dorsey; Park, K T
Abstract: Background: Inadequate infliximab (IFX) drug exposure remains a clinical challenge and leads to high loss of response rates and therapy failure in inflammatory bowel disease (IBD). We aimed to determine the feasibility and pilot effectiveness of a novel, web-based, mobile IFX dosing calculator (mIDC) for therapy optimization. Methods: We developed an mIDC leveraging the known clinical variables of C-reative protein (CRP), albumin, patient's weight, disease activity indices, calprotectin, drug trough levels, and antibodies to IFX that significantly affect pharmacokinetics and/or outcomes. A prospective observational cohort study in pediatric and young adult IBD patients receiving maintenance IFX was performed. System-wide practice adoption of mIDC was achieved through a quality improvement (QI) initiative within a hospital-based infusion unit. Results: Forty-nine patients (median age: 16.0 years; 55% female; 65% Crohn's disease) were followed over 9 months. mIDC recommendations for dose optimization were followed by the treating physicians in 198 (89%) out of 222 infusions. Twenty-eight (13%) of 222 mIDC recommendations were to escalate IFX dosing; 15 (54%) of 28 escalation recommendations were declined, and these patients were more likely to already be receiving IFX dose intensification compared with those in whom escalation recommendations were followed ( P < 0.05). From mIDC initiation to end of follow-up, mean albumin levels remained unchanged at 3.8 g/dL. Median CRP remained unchanged at 2 g/L. Median calprotectin levels showed a downward trend from 30 to 27 μg/g (n = 9, P < 0.05). The percentage of patients undergoing therapeutic drug monitoring in clinical care increased from 34% to 86% with the QI initiative. The target median IFX trough goal of >5 μg/mL was achieved with 81% probability throughout the QI initiative, an increase of 12% compared with pre-QI values. Conclusions: The use of a novel mIDC is feasible and potentially effective, facilitating both standardization and individualization of therapy in clinical care. mIDC appears to be a practical IFX dosing tool for point-of-care use, leveraging individual pharmacokinetic considerations.